2019
DOI: 10.1108/intr-09-2017-0343
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing the Push-Pull-Mooring-Habit framework to explore users’ intention to switch from offline to online real-person English learning platform

Abstract: Purpose The purpose of this paper is to develop an extended Push-Pull-Mooring-Habit (PPMH) framework in order to better understand users’ intention of switching from offline to an online real-person English learning platform service. Design/methodology/approach Based on 301 valid responses collected from an online survey questionnaire, structural equation modeling was employed to examine the research model. Findings The causal model was validated using SmartPLS 3.0, and all study hypotheses were supported.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
128
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(145 citation statements)
references
References 93 publications
15
128
1
1
Order By: Relevance
“…However, mooring directly affects switching intention in the framework of PPM. In addition, previous studies have also indicated that mooring can weaken the relationship between push and pull factors in switching intention (Chen and Keng, 2019;Wang et al, 2019). Therefore, we assumed that previous use habits affect the relationship of the push and pull factors of students using online learning with their switching intention.…”
Section: Mooring Factormentioning
confidence: 96%
See 3 more Smart Citations
“…However, mooring directly affects switching intention in the framework of PPM. In addition, previous studies have also indicated that mooring can weaken the relationship between push and pull factors in switching intention (Chen and Keng, 2019;Wang et al, 2019). Therefore, we assumed that previous use habits affect the relationship of the push and pull factors of students using online learning with their switching intention.…”
Section: Mooring Factormentioning
confidence: 96%
“…Based on the PPM framework, the Push factor is considered a negative influence factor that drives users to leave the existing services. Learning Convenience, Service Quality, and Safety Risks have proven to be push-oriented factors in previous studies (Chen and Keng, 2019;Cheng et al, 2019;Liao et al, 2019). According to the situation, this study regards three variables as the Push factors that affect the willingness of students to switch.…”
Section: Push Factormentioning
confidence: 99%
See 2 more Smart Citations
“…The mooring effect demonstrates switching intentions, which incur switching costs. If a customer has become accustomed to an original online platform and wants to change to another forum, then he/she needs to spend money and time to get used to the new user interface [ 23 ].…”
Section: Literature Reviewmentioning
confidence: 99%